CONCEPÇÕES E PRÁTICAS DE PROFESSORES DA SALA COMUM E DO ATENDIMENTO EDUCACIONAL ESPECIALIZADO (AEE) SOBRE INCLUSÃO ESCOLAR - Ana Lúcia de Arruda Ramos Rezende (2023)
This dissertation refers to the research entitled Conceptions and practices of regular classroom teachers and the Specialized Educational Service (SES) Concepções e práticas de professores da sala comum e do Atendimento Educacional Especializado (AEE) on school inclusion, developed at the Center for Studies and Research in Inclusion (CSRI) Núcleo de Estudos e Pesquisas em Inclusão (NEPI), linked to the line of research Education, Childhood and Diversities of the Graduate Program in Education of the Federal University of Mato Grosso do Sul, Três Lagoas campus. The disparate teachers' conceptions about school inclusion in the researcher's work environment was the problem that originated the research, which sought to answer the question: What are the conceptions about school inclusion that regular classroom teachers and the SES of a public school’s education network have/adopt to organize their pedagogical work? Based on this question, the developed Narrative Research had as general objective to understand which conceptions about school inclusion guide the organization and development of their pedagogical practices. As an instrument for data collection, semi-structured interviews were developed in order to listen carefully to the teachers' reports. In addition, the researcher's field reports were sources of research data. The interpretation of the data produced was based on the production of narratives by the researcher, from the theoretical references used in the study. As a result, I concluded that the teachers' conception of school inclusion is based on training focused on the Medical Model of disability interpretation, which directly influences their pedagogical practices. Teachers think of inclusion as integration, because they idealize a student model and propose the adaptation of activities for those that do not correspond to this idea. They do not know what the Specialized Educational Service is and how this service can help teachers in eliminating the barriers encountered by some students. They assign to the support assistant the function of teaching. In addition, due to lack of knowledge, they do not refute the mistaken orientations of the educational system, such as those that suggest the adaptation of activities for some students. They overvalue the materials and resources believing that they will be enough to deal with the challenges encountered in the classroom, but they are not clear on how to effectively use them. Our conceptions and practices are often contradictory and yet do not always align with inclusion. The research also revealed that teachers are looking for training that helps them deal with the challenges of school inclusion.